Isavuconazole for treatment of rare invasive fungal diseases. Issue 8 (24th July 2018) - Cornely, Oliver A.; Mullane, Kathleen M.; Ostrosky‐Zeichner, Luis; Maher, Rochelle M.; Croos‐Dabrera, Rodney; Lu, Qiaoyang; Lademacher, Christopher; Perfect, John R.; Oren, Ilana; Schmitt‐Hoffmann, Anne‐Hortense; Giladi, Michael; Marty, Francisco M.; et al.
Summary: Data regarding treatment of rare invasive fungal diseases (IFDs) are scarce. We documented the efficacy and safety of isavuconazole for treatment of uncommonly diagnosed IFDs. VITAL was a single‐arm, international, open‐label study evaluating the efficacy and safety of isavuconazole (200 mg orally or intravenously every 8 hours for 48 hours, then once daily). The primary outcome was overall response at Day 42; key secondary outcomes were overall responses at Day 84 and end of treatment (EOT), mortality at Days 42 and 84, and safety. This analysis includes patients with IFD caused by rare or unidentified pathogens. Twenty‐six patients with IFDs caused by rare moulds (n = 17), non‐ Candida yeasts (n = 2), or unidentified moulds (n = 7) were enrolled (median treatment duration [range], 114.5 [1‐496]) days. Overall treatment success was observed in 11/26 (42.3%), 10/26 (38.5%), and 15/26 (57.7%) patients at Days 42, 84, and EOT, respectively. All‐cause mortality rates were 2/26 patients (7.7%) at Day 42 and 4/26 patients (15.4%) at Day 84; another two patients died after Day 84. All patients had ≥1 treatment‐emergent adverse event (TEAE); 15 patients (57.7%) had serious TEAEs, and TEAEs led to discontinuation of isavuconazole in four patients (15.4%). Isavuconazole may be efficacious for treatment of a range of rare IFDs.